Effect of taxation modernization on tax compliance - Sentanu, I Nyoman Wirya; Budiartha, Ketut (International research journal of management, IT and social sciences, 2019)
This study aims to examine the effect of using e-filing, the use of e-billing and administrative fines on individual taxpayer compliance in Badung Regency. Non-compliance with taxpayers can lead to reduced tax potential that can be netted. The transition to a technology-based tax reporting system is expected to help improve tax compliance. The method of data collection in this study is a survey method with questionnaire techniques. The population in this study was 126,477 taxpayers and the sample in this study were 100 taxpayers registered at North Badung KPP and South Badung KPP. The variable use of e-filing is measured by perceptions of usability and perceptions of ease of use. Variables for using e-billing are measured by perceptions of usability and ease of use. Administrative penalty variables are measured by four indicators, namely the function of tax sanctions, sanctions for tax violations, sanctions according to the level of violations and the application of sanctions according to regulations. The analysis technique used is multiple linear regression analysis. The results of the study show that e-filing has a positive effect on taxpayer compliance, e-billing has a positive effect on taxpayer compliance and administrative fines have a positive effect on taxpayer compliance.